Relationship of Environmental Sanitation with Stunting Events in School Children in the Work Area Air Beliti Kab Musi Rawas - Ningsih, Yusria; Fajar, Nur Alam; Novrikasari, Novrikasari (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Environmental sanitation is closely related to nutritional problems. One of the indicators in assessing the degree of public health is the environment, hygiene and sanitation. The purpose of this study was to determine the relationship between environmental sanitation and the incidence of stunting in school children in the Air Beliti PKM Working Area, Musi Rawas Regency. Quantitative research method with cross-sectional design. The population in this study is elementary school age children in 2021 with a total of 200 people. The school's sampling technique was random sampling and the selection of school children was quata sampling of 40 children per class, the sample in this study was 162 students through a randomization process. This research design uses chi square through logistic regression test. Result: There is a significant relationship between environmental sanitation and the incidence of stunting (p=0.004). Conclusion: briefly explained the relationship between stunting and the environment, it is therefore recommended to the puskesmas to always provide socialization on the importance of maintaining and improving environmental sanitation such as waste disposal facilities, latrines and waste water disposal, as well as the importance of providing balanced food so that the development and growth of children is not disturbed and supported by good hygiene behavior of children and families.